2020
DOI: 10.1136/heartjnl-2020-316913
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in TRIM63 cause an autosomal-recessive form of hypertrophic cardiomyopathy

Abstract: ObjectiveUp to 50% of patients with hypertrophic cardiomyopathy (HCM) show no disease-causing variants in genetic studies. TRIM63 has been suggested as a candidate gene for the development of cardiomyopathies, although evidence for a causative role in HCM is limited. We sought to investigate the relationship between rare variants in TRIM63 and the development of HCM.MethodsTRIM63 was sequenced by next generation sequencing in 4867 index cases with a clinical diagnosis of HCM and in 3628 probands with other car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
4
28
0
Order By: Relevance
“…Both gene sets link the cTnI loci to cardiac structure. Finally, DEPICT prioritized several genes in the cTnI loci that were associated with heart development, structure and function, and with cardiovascular diseases: NRAP , which is located in the HABP2 locus, is involved in sarcomere assembly during cardiomyocyte development ( 48 ) and is associated with familial cardiomyopathies ( 49 ), and mutations in TRIM63 have been associated with left-ventricular dysfunction and hypertrophic cardiomyopathy ( 50 ). Likewise, SYNPO2L , which is located in the second most significant locus on chromosome 10, but further away from the index variant than VCL , is involved in sarcomeric signal transduction ( 51 ) and cardiac development ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both gene sets link the cTnI loci to cardiac structure. Finally, DEPICT prioritized several genes in the cTnI loci that were associated with heart development, structure and function, and with cardiovascular diseases: NRAP , which is located in the HABP2 locus, is involved in sarcomere assembly during cardiomyocyte development ( 48 ) and is associated with familial cardiomyopathies ( 49 ), and mutations in TRIM63 have been associated with left-ventricular dysfunction and hypertrophic cardiomyopathy ( 50 ). Likewise, SYNPO2L , which is located in the second most significant locus on chromosome 10, but further away from the index variant than VCL , is involved in sarcomeric signal transduction ( 51 ) and cardiac development ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Matsha et al [ 170 ] and Ding et al [ 171 ] demonstrated that hsa-mir-1299 and hsa-mir-4530 were the miRNAs liable for progression of type 2 diabetes mellitus. Hall et al [ 172 ] and Salazar-Mendiguchía et al [ 173 ] reported that FLNC (filamin C) and TRIM63 were the genes involved in progression of cardio vascular disease, but these genes might be essential for development of obesity associated type 2 diabetes mellitus. Xiao et al [ 174 ], Stratigopoulos et al [ 175 ] and Zhou et al [ 176 ] noted that ATF4, CUX1 and ZBTB7A were the genes responsible for advancement of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…[109], FGF12 [110], AQP4 [111], LMOD2 [112], SELENBP1 [113], MB (myoglobin) [114], S100A1 [115], RYR2 [116], GPC5 [117], JARID2 [118], EGFR (epidermal growth factor receptor) [119], FUNDC1 [120], S1PR1 [121], EPAS1 [122] and OSBPL11 [123] genes are a potential biomarkers for the detection and prognosis of HF at an early age. A previous study reported that CALR (calreticulin) [124], BSCL2 [125], PKD1 [126], TMBIM1 [127], CHST15 [128], NAA10 [129], TCF3 [130], CNN1 [131], TAF1A [132], ACAD9 [133], KLHL24 [134], MYOM2 [135], TRIM63 [136] [210] are the key biomarkers in cardiac hypertrophy. Previous studies had shown that the expression of CLIC1 [211], ARPC1B [212], FLNA (filamin A) [213], HILPDA (hypoxia inducible lipid droplet associated) [214], RTN3 [215], G0S2 [216], CALU (calumenin) [ [239], NCOA2 [240], ZBTB16 [241], TFAM (transcription factor A, mitochondrial) [242], RASAL2 [243], NDUFB6 [244], HELZ2 [245] and CIITA (class II major histocompatibility complex transactivator) [246] were reported to be expressed in obesity, but these genes might be novel target for HF.…”
Section: Discussionmentioning
confidence: 99%